Reinforcement learning in the metaverse - Goyal, Bhavya (Nanyang Technological University, 2023)
In-depth research has been done on AR applications using wireless networks recently to boost user satisfaction, however, neither of the preceding studies took into account how different the edge computing service requirements exists among users, additionally, they do not take sequential scenarios into account or apply reinforcement learning (RL) strategies to the suggested task hence, the aim of this research is to propose a model which enhances the user satisfaction while socializing in the Metaverse. This research project also aims to compare various pre-existing reinforcement learning algorithms with a novel Quality of Service (QoS) model for AR socialization on a multichannel wireless network.